SYNTHESIS OF MESOPOROUS METHYL-SILICA HYBRID FOR ADSORPTION OF ALIZARIN RED-S - Bambang Rusdiarso; Eko Sri Kunarti; Saprini Hamdiani (Universitas Gadjah Mada, 2008)
Mesoporous methyl-silica hybrid has been synthesized through sol-gel process, by using tetraethylorthosilicate and methyltriethoxysilane as precursors and tartaric acid as a template. The adsorbent was applied to study the adsorption of alizarin red-S. The preparation of methyl-silica hybrid was carried out at various mol ratios of precursors and tartaric acid concentration. The methyl-silica hybrid result was characterized by infrared spectroscopy, X-ray diffraction, and surface area analyzer. Adsorption experiment was conducted to study the effect of pH and Alizarin Red-S concentration on the adsorption capacity of the adsorbent. The adsorbed Alizarin Red-S was calculated from different of Alizarin Red-S concentration before and after adsorption based on the analysis with UV-Vis method. Characterization with Infrared Spectroscopy showed that methyl-silica hybrid has been successfully synthesized as indicated by appearance of characteristic functional group vibrations i.e Si-C, silanol (Si-OH) and siloksan (Si-O-Si). The X-ray diffraction data showed amorphous structure of methyl-silica Hybrid. The Surface Area Analyzer analysis data showed that the pore diameter and surface area of methyl-silica hybrid tended to increase as the template concentration increases. Adsorption study of methyl-silica hybrid showed that the adsorption decreased as the pH was increased. The optimum adsorption was obtained at pH=2.0 with the concentration of Alizarin Red-S of 70 mg/L.